Recombinant DNA biotechnology : - Kreuzer, Helen (ASM Press, 1996)
Burlington, NC. Basic text focusing on the fundamentals of molecular biology and modern biotechnology. Includes activities, basic laboratory procedures and questions. For undergraduates. Softcover.